Comparative evaluation of antibacterial efficacy of active oxygen containing versus other dentifrices against Streptococcus mutans count in children with early childhood caries: A clinico-microbiological study - Tanvi Jindal; Nikhil Srivastava; Vivek Rana; Noopur Kaushik; Preeti Sharma; Tushar Pruthi (Wolters Kluwer Medknow Publications, 2023)
Background: Fluoridated dentifrices have been used for the prevention of dental caries since ages. However, to avoid the risk of fluorosis, the use of newer nonfluoridated options in dentifrices has shown a great interest in reducing Streptococcus mutans (SM) in early childhood caries (ECC). Aim: The study aimed to evaluate the antimicrobial efficacy of active oxygen (AO)-based dentifrice with amine fluoride (AF)-, sodium monofluorophosphate (SMP)-, herbal (HB)-, and tricalcium phosphate (TCP)-based dentifrices on SM count in children with ECC. Materials and Methods: Two hundred and fifty children aged 3-6 years with def ≥4 were selected and randomly divided into five groups of 50 each, based on the type of dentifrices used; Group I: AO-based, Group II: TCP, Group III: SMP, Group IV: AF, and Group V: HB dentifrice, and were asked to brush twice daily for 15 days. The saliva samples were collected at baseline, and after 15 days, cultured for SM colonies count. Results: Difference in colony-forming units (CFU)/ml between baseline and 15 days was highly significant in all the five groups (P < 0.001). Significant difference was observed in SM count after 15 days between Groups I and IV (P = 0.017), while nonsignificant differences were seen when compared with Groups II, III, and V (P = 0.975, 0.137, and 0.992). Conclusions: All the dentifrices were efficacious in reducing SM count in children with ECC. Although AO dentifrice showed superior results when compared to SMP, TCP, and HB, it did not prove to be superior to AF.